Promoción y la demanda turística de la ciudad de Iquitos, 2020 - Bonifas Chujutali, Nidia Stefany (2021)
The general objective of this research was to determine the relationship between tourism promotion and demand in the city of Iquitos, 2020; opting for a descriptive correlational research and non-experimental design, for which a sample of 17 workers from three institutions related to tourism has been taken, who were surveyed through a questionnaire that analyzes their perception regarding the variables evaluated ; managing to conclude that there is a relationship between tourism promotion and demand in the city of Iquitos, in 2020; which is contrasted by a significance of 0.000 and a correlation coefficient (Spearman's Rho) of 0.911 which is very high positive; In other words, since promotion is deficient, the tourist demand will be lower. Likewise, it is determined that the development of tourism promotion is regular (41%) with a tendency to be deficient (35%), due to the fact that the use of tourist information dissemination tools is minimal, making it difficult to generate interest in tourists for visit the tourist attractions offered by the city of Iquitos and its surroundings. Finally, it is determined that the tourist demand is regular (47%) with a tendency to be low (41%), since little influx of tourists is evidenced, given that their preference and expectations of tourism are high and normally the city of Iquitos Institutionally it is not prepared to satisfy the demand generated.